Solid-Liquid Phase Equilibria for the Ternary System KNO3 + KH2PO4 + H2O at 283.15, 298.15, and 313.15 K - Jun-feng Wan; Fei Wang (Journal of Chemistry)
The solid-liquid phase equilibria of the ternary system KNO3 + KH2PO4 + H2O at the temperatures of 283.15, 298.15, and 313.15 K and the pressure of  0.1 MPa are researched by isothermal solution saturation. The equilibria solid phases are researched by Schreinemakers method (wet residues). The solubility data are determined. Based on these data, the phase diagrams and the crystalline areas are determined. The phase equilibria at different temperatures are compared and discussed. All results can provide basic data support for crystallization and further researches.